Agrowastes as substrates for hydrolytic enzymes and biomass production of native isolates of Trichoderma spp. - DEEPIKA SHARMA, SACHIN GUPTA and S.A. MALLICK*, MONI GUPTA, SURUCHI MAHAJAN (Indian Phytopathology, 2016)
Trichoderma spp. is one of the best known and well described biocontrol fungi for its antagonistic properties against phytopathogens. For selection of suitable, cheaper and easily available substrate for the mass multiplication of Trichoderma spp., locally available substrates viz. sugarcane baggase, wheat bran, rice bran and sorghum were evaluated for C:N ratio, mass multiplication potential under solid fermentation and their abilty to induce the production of hydrolytic enzymes viz. Cellulase, Chitinase, b-1, 3-glucanase under liquid fermentation. Among the substrates evaluated, highest C: N ratio was recorded in sugarcane baggase (233.49: 1) and lowest in sorghum grain (11.56: 1). Maximum biomass production of Trichoderma spp. was observed in wheat bran (1.76g/100 ml of broth) followed by rice bran (1.67g/100 ml of broth) and sorghum grains (1.62g/100ml of broth). However, lowest biomass yield was observed in the sugarcane baggase (1.01g/100ml of broth). Specific activities of the enzymes under study were reported to be maximum on 6th day of incubation. Cellulase activity was highest in the isolate AG52 (3.957 U/mg protein) followed by FL60 (3.151 U/mg protein). Highest chitinase activity was observed in AG52 (3.458 U/mg protein) followed by VE56 (2.728 U/mg protein). However, glucanase activity was highest in VE56 (2.995 U/mg protein) followed by AG52 (2.642 U/mg protein) and FL60 (2.538 U/mg protein).